Ukrainian startup ecosystems: regional development and European integration - D. A. Donets (Економічний вісник Державного вищого навчального закладу Український державний хіміко-технологічний університет)
Building innovation economy represents strategic priority for Ukraine’s European integration amidst wartime challenges. Ukraine’s startup ecosystem demonstrates potential valued at €28 billion, ranking among Central-Eastern Europe’s top three, yet regional disparities constrain development. Russian invasion created challenges but revealed exceptional technological resilience. This study analyzes current state and regional characteristics of Ukraine’s startup ecosystem, identifies disparities and competitive advantages, develops recommendations for optimization within European innovation space integration framework. Research employs mixed-methods approach integrating quantitative analysis with qualitative assessment through SWOT analysis, comparative evaluation, expert assessments using nine parameters: human capital, education, financing, infrastructure, mentorship, culture, regulation, markets, networks. Data sources include international reports (StartupBlink, Dealroom, Civitta), investment analytics, statistics covering 2020-2024. Findings reveal regional concentration with Kyiv hosting 40% of startups. Investment recovery: 2024 investments reached $462 million (120% growth). Sectoral distribution: IT/software (35%), artificial intelligence (15%), fintech (12%). Defense technology emerges with 820+ projects attracting $59 million in 2024. Study provides first systematic regional analysis during wartime transformation, introducing four-component optimization model for European integration. Scientific novelty: crisis-resilient assessment methodology for innovation continuity under extreme conditions. Findings offer strategic roadmap for institutions and stakeholders to enhance competitiveness and accelerate European integration providing framework for post-war reconstruction.